Four new rupicolous species of Pleroma (Melastomataceae) endemic to Espírito Santo, Brazil - Meyer, Fabrício Schmitz; Kollmann, Ludovic J.c.; de Fraga, Claudio Nicoletti; Goldenberg, Renato (Phytotaxa, 2018)
Four new species from the complex around Pleroma heteromallum, endemic from Espírito Santo, Brazil, are described: Pleroma cucullatum, P. fontanae, P. fornograndense and P. venetiense. All these new species are rupicolous, grow in vegetation associated with inselbergs, and are endangered. We present descriptions, taxonomic comments, illustrations, conservation status assignments for the new species, and an identification key for the species of Pleroma in Espírito Santo with stamens with glandulose pedoconnective and appendages, similar to the new species